2014
DOI: 10.1080/03235408.2014.882121
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors influencing population density of the peach fruit fly (PFF),Bactrocera zonata(Saunders) (Diptera: Tephritidae) in Assiut, Northern Upper Egypt

Abstract: The results of this study showed that the attracted males exhibited a different response to the examined factors at two trap heights and during both study seasons (2011 and 2012) of study. However, statistical analysis indicated that the maturity level of guava fruits was the most effective variable in attracting males to methyl eugenol (ME)-baited traps hung at 1 and 2 m heights and had an effect on the average number of attracted males at the two height levels. The common rank of the independent variables ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…We also found significant differences in the effectiveness of traps suspended at different heights, with the greatest number of flies caught 1 to 1.5 m above the soil, a finding consistent with the most effective trapping height of 1 to 2 m reported by Darwish et al (2015). The high fruit fly capture rate also may be related to the flight height of Drosophila fruit flies, though we have no data on this.…”
Section: Discussionsupporting
confidence: 79%
“…We also found significant differences in the effectiveness of traps suspended at different heights, with the greatest number of flies caught 1 to 1.5 m above the soil, a finding consistent with the most effective trapping height of 1 to 2 m reported by Darwish et al (2015). The high fruit fly capture rate also may be related to the flight height of Drosophila fruit flies, though we have no data on this.…”
Section: Discussionsupporting
confidence: 79%
“…al.,(2014). The effect of weather factors on population of fruit flies during summer season insignificantly varied, thus indicating that these weather factors were not entirely the major factors that controlling the population fluctuations of both fruit flies (Afia, 2007 andAmin, 2008), guava rate of maturation was the most independent variables for attracting B. zonata adults during summer season (Darwish et al, 2014). However, most of those investigators concluded that weather factors particularly, temperature, relative humidity, sunlight, rainfall and soil temperature are significantly correlated with population fluctuation of fruit fly species.…”
Section: Discussionmentioning
confidence: 97%
“…At Fayoum governorate, guava trees are randomly distributed in minor areas or cultivated in scarce form as inter-planting mango areas. B. zonata populations are reaching high levels in July to September attacking guava fruits causing a significant damage coinciding maturation of guava fruits (Saafan et al, 2006, Afia, 2007, Amin, 2008and Darwish et al, 2014. This causes great losses to the growers because the fruits are unmarketable.…”
Section: Introductionmentioning
confidence: 99%
“…Infected fruits (fallen fruit) must be collected and should be buried deep down to the 1-1.5m pit in such a way that the infected fruit remains at least 30cm below the surface. Pupa can not emerge to adults from the soil depth more than 30cm (Darwish et al, 2015). If the procedure of deep burial is followed, the infected fruits can also be used for compost making.…”
Section: Prevention Of Spreadmentioning
confidence: 99%